Using Clusters In Teaching Russian Language - Navruzova Farida Nazarovna (Zien Journals, 2025)
In connection with the introduction of new educational standards, new requirements are imposed on the education system as a whole, and on the specifics of teaching Russian in particular.
Keywords: Russian language; innovation; learning